Algoritma sebagai Subjek Etis: Analisis Filsafat Komunikasi terhadap Moralitas Sistem Kecerdasan Buatan - Susanto, Gabriel Abdi (Dekonstruksi, 2025)
Algorithms in artificial intelligence (AI) systems are increasingly playing a role in shaping the landscape of digital communication. However, studies in communication philosophy often treat algorithms merely as technical tools rather than ethical subjects. This article examines how algorithms, particularly in social media, contribute to shaping public opinion, fostering social polarization, and carrying ethical implications. Using a communication philosophy approach, the article highlights the moral aspects of algorithms and the challenges and opportunities in creating more ethically responsible AI systems.